Kajian Dampak Keberadaaan Perkebunan Tebu Terhadap Kondisi Sosial Ekonomi Masyarakat Kecamatan Gondanglegi Kabupaten Malang: Study of the Impact of Sugarcane Plantations on the Socio-Economic Conditions of the Community in Gondanglegi District, Malang Regency - Rizkiyah, Noor; Rozci, Fatchur (Jurnal Ilmiah Manajemen Agribisnis, 2025)
The existence of sugar cane plantations as crops cultivated by the people, government, and private sector has an impact on the socio-economic conditions of the community. The purpose of this study is to examine the existence of sugar cane plantations in Gondanglegi Kulon Village, Gondanglegi Subdistrict, on the socio-economic conditions of the community. A qualitative approach with focus group discussions and in-depth interviews as well as data validity was used in this study. The results of the study show that the existence of sugar cane plantations and sugar factories has brought about social changes for the surrounding community and has had a positive economic impact by creating diversity in livelihoods, thus providing more varied opportunities that are in line with the capacity of family members to meet household economic needs.